Aromat zbrodni ("Pachnidło" Toma Tykwera i "Jasminum" Jana Jakuba Kolskiego) = The aroma of crime ("Perfume" by Tom Tykwer and "Jasminum" by Jan Jakub Kolski) - Radziszewski, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the study is the novel by Patrick Süskind "Perfume", filmed in two versions: TomTykwer`s "Perfume" and "Jasminum" by Jan Jakub Kolski. Jean Baptiste Grenouille, the main charakter of "Perfume", is a brilliant artist and felon looking for perfection who, by committing suicide, carries out the negation of humanity. Brother Health, one of the characters of "Jasminum", is a humble and hard-working monk, on whom the grace of mystical holiness is bestowed by the Divine Providence.
Keywords: Süskind, Patrick (1949- ); "Pachnidło"; adaptacja filmowa